Internal Auditing and Institutional Performance of Local Governments in Ghana - Anthony Egyir Aikins; John Victor Mensah (Indonesia Auditing Research Journal, 2023)
Local governments are required to add value to the public good. Internal auditing is a mechanism used to monitors operations of local governments to provide quality municipal services. However, poor delivery by local governments has necessitated this paper to examine the link between internal auditing and institutional performance of four selected local governments in the Central Region of Ghana. Using interpretivism philosophy and in-depth interview design, purposive sampling procedure was used to select 12 key informants to provide primary data using interview guide. The key informants were two internal auditors, two Metropolitan, Municipal, and District Co-ordinating Directors, four Chairpersons of Audit Committees, three District Auditors, and one Regulator at national level. Secondary data were also collected from various documents through library search. Data were analysed manually using content analysis and pattern matching. The study revealed that the internal auditing carried out did not enhance performance of the selected local governments as they did not perform the day-to-day functions to expectation and sanctions were not applied to perpetrators of irregularities in operations. The performance of local governments is supposed to be enhanced if internal audit recommendations are implemented by management and perpetrators of irregularities are sanctioned.